Advertising Campaign as Multi-Stage Process - M. N. Kim (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
Modern advertising market must not to have a spontaneous self-regulation on the part of the participants, because this leads to inconsistency of their actions. Therefore, in the first place, when we organization of the advertising campaign, the clear plan is put forward. This planning involves the development of objectives, and the ways to achieve them, also the choice of means of advertising, and planning of each stages of an advertising campaign, finally, forecasting results. This makes it possible, on the one hand, to streamline the entire advertising process, and on the other — to organize the work of each participant to achieve effective results.